The Influence of Monetary Policy on the Sustainable Economic Development of the Country in the Context of Globalization - Margineanu, Aureliu; Cernit, Rodica; Moroi, Tatiana (The Journal of Accounting and Management, 2024)
This paper analyzes the influence of monetary policy on the sustainability of a country’s economic development in the current conditions of globalization. The theoretical aspects and empirical data are examined, illustrating how monetary policy contributes to achieving macroeconomic stability, economic growth, and reducing inflation levels. The relevance of the topic is determined by the impact of both internal and external factors. Understanding and applying them in a real and objective manner allow for the investigation of the rationality and correctness of the development directions of the economy, as well as the optimal use of the financial resources of the banking system. The raising of questions and analysis regarding the evaluation and efficient use of the economic resources of credit organizations is driven by the need to establish the real possibilities of the banking system in the Republic of Moldova to support the economy’s exit from the crisis and its structural modernization with minimal costs. However, this, in turn, requires a comprehensive analysis of the situation, an objective evaluation of the existing resources, and the formation of development directions for the economic potential of the country’s banking system.